2010
DOI: 10.1111/j.1365-2966.2010.16667.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy group at z=0.3 associated with the damped Lyman α system towards quasar Q1127-145

Abstract: We performed a spectroscopic galaxy survey, complete to mF814W≤ 20.3 (LB > 0.15L★B at z= 0.3), within 100 × 100 arcsec2 of the quasar Q1127–145 (zem= 1.18). The Very Large Telescope/Ultraviolet and Visual Echelle Spectrograph (UVES) quasar spectrum contains three zabs < 0.33 Mg ii absorption systems. We obtained eight new galaxy redshifts, adding to the four previously known, and galaxy star formation rates (SFRs) and metallicities were computed where possible. A strong Mg ii system [Wr(2796) = 1.8Å], which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 98 publications
(199 reference statements)
10
43
0
Order By: Relevance
“…For instance, Whiting et al (2006) found at least five galaxies at the redshift of a W = 2.5Å Mg ii absorber. Similarly, Kacprzak et al (2010) found five low-mass galaxies associated with a W = 1.8Å absorber. Nestor et al (2011) found ultra-strong Mg ii absorbers with W = 3.6, 5.6Å in two systems associated with massive galaxy pairs, and lastly Gauthier (2013) found another very strong absorber with W = 4.2Å in a group of three galaxies.…”
Section: A High Fraction Of Strong Mg II Absorbers In Galaxy Groupsmentioning
confidence: 81%
See 1 more Smart Citation
“…For instance, Whiting et al (2006) found at least five galaxies at the redshift of a W = 2.5Å Mg ii absorber. Similarly, Kacprzak et al (2010) found five low-mass galaxies associated with a W = 1.8Å absorber. Nestor et al (2011) found ultra-strong Mg ii absorbers with W = 3.6, 5.6Å in two systems associated with massive galaxy pairs, and lastly Gauthier (2013) found another very strong absorber with W = 4.2Å in a group of three galaxies.…”
Section: A High Fraction Of Strong Mg II Absorbers In Galaxy Groupsmentioning
confidence: 81%
“…These works found that the closest galaxy is at d = 30 − 70 kpc. In the work by Kacprzak et al (2010) a galaxy is found a smaller impact parameter (17.4 kpc). However, from an analysis of the metallicity of the absorber and of the group galaxies, the authors concluded that the closest galaxy is not hosting the absorber, which is more likely to arise from tidal debris in the group environment.…”
Section: A High Fraction Of Strong Mg II Absorbers In Galaxy Groupsmentioning
confidence: 93%
“…All five galaxies (z ∼ 0.3) are at impact parameters 115 < b < 265 kpc with L < 0.3L * , which is consistent with Mg II absorption occuring in luminous galaxies within 100 kpc impact parameter, but not beyond. On the other hand, the simulations by Kacprzak, Murphy & Churchill (2010) show that DLAs can occur even at 200 kpc impact parameters.…”
Section: Galaxies With No Absorption Counterpartsmentioning
confidence: 95%
“…It is not uncommon for studies to find galaxies with no Mg II absorption in fields of QSOs. Kacprzak, Murphy & Churchill (2010) identify five galaxies along the line of sight to Q1127-145 with no absorption. All five galaxies (z ∼ 0.3) are at impact parameters 115 < b < 265 kpc with L < 0.3L * , which is consistent with Mg II absorption occuring in luminous galaxies within 100 kpc impact parameter, but not beyond.…”
Section: Galaxies With No Absorption Counterpartsmentioning
confidence: 99%
“…Literature references: a Kacprzak et al (2011), b Lane et al (1998), c Muzahid et al (2016), d Rao et al (2006), e Boisse et al (1998), f Rahmani et al (2018b), g Péroux et al (2019). 1 Observed magnitudes in HST F814W fromKacprzak et al (2010)…”
mentioning
confidence: 99%